DETERMINAN STATUS GIZI PADA SISWA SEKOLAH DASAR - Zulfa Amira (Jurnal Kesehatan, 2024)
Malnutrition remains a central issue. There are various factors that cause this problem to become very complex. The research problem is what factors are related to nutritional status. The aim of the research was to determine factors related to nutritional status in elementary school children. This research is qualitative research presented in descriptive form. The data collection method was carried out by means of in-depth interviews, observation and document review. Data analysis techniques using content analysis include data collection, data analysis, data reduction, data verification, then drawing conclusions. The research conclusion is that the variables related to nutritional status are the mother's level of knowledge, mother's education, family income, infectious diseases, energy consumption level, and protein consumption level.